Evaluasi Dosis Radiasi Hambur Pemeriksaan CT Scan Thorax pada Organ Gonad dan Tiroid - Magfirah, Magfirah; Adrial, Rico; Ulya, Syarifatul (Universitas Andalas, 2025)
Research has been carried out regarding the evaluation of scattered radiation dose during CT scans of the thorax on the gonads and thyroid using 30 patients with CT scans of the thorax. In this study, the radiation dose received by thorax CT Scan patients was measured using TLD-100 which was placed at 3 measurement points on the patient. The first point was placed on the thyroid using 1 TLD, the second point on the thorax using 2 TLDs, and the third point was placed on the gonads using 1 TLD. The thorax CT Scan examination used a tube voltage of 120 kV. The results showed that the DLP and CTDIvol values ​​affected the value of the effective dose received. The average values ​​of CTDIvol and DLP were 6.268 mGy and 782.196 mGy.cm and the average thorax dose was 2.495 mSv. The average CTDIvol and DLP values ​​obtained in the study did not exceed the threshold set by the BAPETEN Regulation in 2021, namely the CTDIvol and DLP values ​​were 16 mGy and 810 mGy.cm. Radiation that affects the gonads and thyroid organs is scattered radiation. The average radiation dose received on the gonads and thyroid organs was 0.121 mSv and 0.485 mSv. The average dose value received did not exceed the dose received on the thorax and the radiation dose received on the thyroid was greater than the radiation dose received on the gonads. This is because the thyroid organ is closer to the irradiation area than the gonad organ.